Whatever happened to repeat victimisation?. Issue 4 (November 2018) - Pease, Ken; Ignatans, Dainis; Batty, Lauren
Abstract Crime is concentrated at the individual level (hot dots) as well as at area level (hot spots). Research on repeat victimisation affords rich prevention opportunities but has been increasingly marginalised by policy makers and implementers despite repeat victims accounting for increasing proportions of total crime. The present paper seeks to trigger a resurgence of interest in research and initiatives based on the prevention of repeat victimisation.